BIOCENOTIC INTERACTIONS AND AGROECOSYSTEM ROLES OF PENTATOMOIDEA (HETEROPTERA) STINK BUGS IN THE WESTERN FERGANA REGION (Scientific journal of the Fergana State University, 2025)
This study examines the species composition, ecological characteristics, and role of Pentatomoidea (Heteroptera) stink bugs in the agroecosystems of Western Fergana. The research analyzed the significance of phytophagous and entomophagous species in various ecosystems, their role in food chains, and their impact on agroecosystems. The population dynamics of these bugs, their effects on agricultural crops, and the efficiency of entomophagous species in biological control were assessed. The obtained results are essential for ensuring agroecosystem stability, developing biological pest control strategies, and effectively organizing regional entomofauna monitoring. The study findings were analyzed based on scientific literature and field observations.